Barriers to accrual and enrollment in brain tumor trials. Issue 9 (7th June 2019) - Lee, Eudocia Q; Chukwueke, Ugonma N; Hervey-Jumper, Shawn L; de Groot, John F; Leone, Jose Pablo; Armstrong, Terri S; Chang, Susan M; Arons, David; Oliver, Kathy; Verble, Kay; Musella, Al; Willmarth, Nicole; et al.
Abstract: Many factors contribute to the poor survival of malignant brain tumor patients, some of which are not easily remedied. However, one contributor to the lack of progress that may be modifiable is poor clinical trial accrual. Surveys of brain tumor patients and neuro-oncology providers suggest that clinicians do a poor job of discussing clinical trials with patients and referring patients for clinical trials. Yet, data from the Cancer Action Network of the American Cancer Society suggest that most eligible oncology patients asked to enroll on a clinical trial will agree to do so. To this end, the Society for Neuro-Oncology (SNO) in collaboration with the Response Assessment in Neuro-Oncology (RANO) Working Group, patient advocacy groups, clinical trial cooperative groups, including the Adult Brain Tumor Consortium (ABTC), and other partners are working together with the intent to double clinical trial accrual over the next 5 years. Here we describe the factors contributing to poor clinical trial accrual in neuro-oncology and offer possible solutions.